2019
DOI: 10.1016/j.jaac.2018.07.897
|View full text |Cite
|
Sign up to set email alerts
|

Sertraline Effects on Striatal Resting-State Functional Connectivity in Youth With Obsessive-Compulsive Disorder: A Pilot Study

Abstract: Objective: Foundational knowledge on neural circuitry underlying pediatric obsessivecompulsive disorder (OCD) and how it changes during standard treatment is needed to provide the basis for conceptualization and development of novel, targeted treatments. This study explored the effects of sertraline, a selective serotonin reuptake inhibitor, on resting-state functional connectivity (RSFC) in cortico-striatal-thalamic-cortical circuits in pediatric OCD. Method: Medication-free youths with OCD (n=14) and healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…Citalopram primarily reduces connectivity with the sensorimotor network and structures that are related to self‐referential mechanisms (Klaassens et al., 2017). Bernstein et al report that sertraline has effects on resting‐state functional connectivity in OCD, demonstrating increased striatal connectivity from baseline to 12 weeks compared with controls including the right putamen with the left frontal cortex and insula and the left putamen with the left frontal cortex and pre‐ and postcentral cortices (Bernstein et al., 2019). In the present study, no different cluster based on ALFF was found in patients with pharmacotherapy, which might be related to the fact that 75% of the patients were taking SSRIs when they entered the clinical trial.…”
Section: Discussionmentioning
confidence: 99%
“…Citalopram primarily reduces connectivity with the sensorimotor network and structures that are related to self‐referential mechanisms (Klaassens et al., 2017). Bernstein et al report that sertraline has effects on resting‐state functional connectivity in OCD, demonstrating increased striatal connectivity from baseline to 12 weeks compared with controls including the right putamen with the left frontal cortex and insula and the left putamen with the left frontal cortex and pre‐ and postcentral cortices (Bernstein et al., 2019). In the present study, no different cluster based on ALFF was found in patients with pharmacotherapy, which might be related to the fact that 75% of the patients were taking SSRIs when they entered the clinical trial.…”
Section: Discussionmentioning
confidence: 99%
“…A major strength of the current study is that investigation of a medication-naïve sample ensured that reported results are not driven or confounded by the effects of pharmacotherapeutic intervention on brain response (Bernstein et al, 2019). However, due to the challenge of recruiting medication-naïve participants at a tertiary care centre resulting in the small sample examined here, interpretation of our results must take into account the potential for inflated false positives in a small exploratory example.…”
Section: Discussionmentioning
confidence: 99%
“…However, magnetoencephalography (MEG) may offer some advantages over fMRI as it records neuromagnetic activity and enables tracking of neural activation with high spatial and temporal resolution (Ahlfors and Mody, 2019). Additionally, MEG can characterize the frequencies in which large groups of neurons fire during a particular task, including oscillations in the: delta (0.5-3 Hz), theta (4-7 Hz), alpha (8)(9)(10)(11)(12), beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29), and gamma (30+ Hz) bandwidths (Todd et al, 2014). Thus far, very few studies have used MEG to study neural response in OCD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study had several strengths. First, our OCD sample was free of psychotropic medications at the MRI scan, which is important given the effects of SSRIs on brain structure and connectivity (e.g., Bernstein et al, 2018;Lugo-Candelas et al, 2018). Second, this study used high-resolution data and the most up-to-date analysis methods (FreeSurfer v6.0 and MRtrix3), allowing for improved data quality and segmentation/parcellation.…”
Section: Discussionmentioning
confidence: 99%